Genetic diagnosis of Fanconi anemia. Literature review - A. V. Panferova; N. M. Timofeeva; Yu. V. Ol’shanskaya (Онкогематология, 2016)
The literature review provides information on genetic diagnosis of Fanconi anemia: currently used methods of genetic analysis, spectrum and frequency of mutations, including in different populations, and order of molecular genetic methods are described. Problems of genetic diagnosis of Fanconi anemia in the world and in particular in the Russian Federation are also presented.